TRANSFORMATIONAL, AUTHENTIC, AND AUTHORITARIAN LEADERSHIP: WHICH ONE IS THE MOST INFLUENTIAL IN STAFFS’ SCHOOL PERFORMANCE IN JAKARTA INDONESIA - Agus Purwanto; Rubi Mirayani Sinnuaji; Anggaripeni Mustikasiwi; Williana Liem (Universitas Muhammadiyah Kalimantan Timur, 2020)
The research conducted in a religion based school in Gading-Serpong, Jakarta was conducted to determine the significance of leadership style toward the organizational culture and motivation in order to see the influence on the staff’s performance. Data obtained through questionnaires with total sampling method of 33 out of 34 employees. Data analysis is using Spearman Rank correlation analysis, correlation, and hypothesis testing. The result of the study showed that (1) the authentic leadership style is perceived higher than authoritarian and transformational leadership styles (2) The leadership style has a significant influence on the school staff’s motivation. This is indicated on the result of P-value that is 0.0000.(3) The leadership style does have an influence on the organizational culture as the the P value between dependent variable Leadership (KP) to independent variable Performance (KJ) with the intervening variable Culture Organization (BO) is 0.004 and it means there specific Indirect Effect is accepted since it is less than 0.005. whereas the P value between the dependent variable Leadership (KP) to independent variable Performance (KJ) with the intervening variable Motivation (MO) is 0.124. (4) The leadership style has also showed to have significant influence and direct effect on the staff’s performance. This is depicted by the result of the P values that is 0.001, which explained that leadership has a significant and direct effect on the workers’ performance, (5) The organizational culture has an influence toward the staff’s performance as based on the data, from all the result of the R-square for the Organizational culture (BO) is 0.56; that organizational culture as the intervening variable by 56% and (6) the staff’s motivation does not affect the staff’s performance as shown on the the P value is 0,082 which is more than 0.05, therefore Motivation of the staff does not affect the performance of the staff directly.